Atom probe tomography of stress corrosion crack tips in SUS316 stainless steels - Meisnar, M; Moody, M; Lozano-Perez, S (Elsevier, 2015)
Novel atom probe tomography (APT) data of an intergranular stress corrosion crack tip has been acquired. Using APT for stress corrosion cracking research, very small, localized features and their distribution around the crack tip can be studied in 3D. This work details the development of a technique for the preparation of atom probe needles. Initial characterization via analytical transmission electron microscopy provides with a complementary analysis and accurately locates features that can be correlated with the reconstructed APT data. Ni enrichment and intergranular oxidation ahead of the crack tip have been studied with APT in 3D and with near-atomic resolution.